O pająku, duszy i łacińskiej konstrukcji accusativus cum infinitivo, czyli jak zrozumieć jeden z wersetów Psałterza floriańskiego - Kuźmicki, Marcin (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2009)
The author of the article, through the analysis of one of the verses from Psałterz floriański (“Florian Psalter”), is trying to understand where the difficulties in understanding this old Polish text arise. Is it exclusively the fault of a medieval translator and the Polish written language that had not been completely formed by then or rather is it a contemporary reader that is to blame? Taking into account at least a number of aspects connected with the work of a medieval translator and copyist , such as: the lack of a consistent Latin base text—the canonical version, widely known, that is to appear no sooner than in the print era; insufficient knowledge of Psałterz floriański by heart; different structures of the Latin language which the translator tried to express by choosing Polish words that would not violate the structure of the translation base—all these factors make the author of the article defend the medieval writer whose work requires in-depth and repetitive reading before it starts revealing its secrets to the modern reader.